Behavioral and Institutional Perspectives on QRIS Adoption among MSMEs in Indonesia: A Qualitative Descriptive Study - Dedi Harianto; Ahmad; Zohaib Hassan Sain (International Journal For Advanced Research, 2026)
The rapid development of digital payment systems has transformed financial transactions among micro, small, and medium enterprises (MSMEs) in Indonesia. One of the most significant innovations is Quick Response Code Indonesian Standard (QRIS), which aims to promote payment efficiency and financial inclusion. This study explores behavioral and institutional perspectives on QRIS adoption among MSMEs in Indonesia using a qualitative descriptive approach. Data were collected through in-depth interviews with MSME owners across various business sectors, supported by interviews with relevant institutional stakeholders and analysis of policy documents related to QRIS implementation. The data were analyzed using thematic analysis to identify key patterns and recurring themes. The findings reveal that MSMEs’ adoption of QRIS is strongly influenced by behavioral factors such as perceived ease of use, transaction convenience, customer demand, and trust in digital payment systems. In addition, institutional factors including government support, banking infrastructure, socialization programs, and regulatory frameworks play a crucial role in encouraging QRIS utilization. However, challenges remain, particularly related to digital literacy gaps, internet accessibility, and concerns over transaction fees and technical disruptions. This study contributes to the growing literature on digital payment adoption in developing economies by providing contextual insights into how behavioral and institutional dynamics shape MSMEs’ engagement with QRIS. The findings offer practical implications for policymakers, financial institutions, and stakeholders in designing more inclusive digital payment strategies and strengthening MSMEs’ participation in the digital economy.